The ecdysone receptor complex is essential for the reproductive success in the female desert locust, Schistocerca gregaria - Lenaerts, Cynthia (Sci Rep, 2019)
Ecdysteroid hormones influence the development and reproduction of arthropods by binding a heterodimeric complex of nuclear receptors, the ecdysone receptor (EcR) and the retinoid-X-receptor/ultraspiracle (RXR/USP). Here, we report on the in vivo role(s) of the ecdysone receptor complex, SchgrEcR/SchgrRXR, in the female reproductive physiology of a major phytophagous pest insect, i.e. the desert locust, Schistocerca gregaria. Tissue and temporal distribution profiles were analysed during the first gonadotrophic cycle of adult female locusts. RNA interference was used as a reverse genetics tool to investigate the in vivo role of the ecdysone receptor complex in ovarian maturation, oogenesis, fertility and fecundity. We discovered that silencing the ecdysone receptor complex in S. gregaria resulted in impaired ovulation and oviposition, indicative for a crucial role of this complex in chorion formation. We also found evidence for a feedback of SchgrEcR/SchgrRXR on juvenile hormone biosynthesis by the corpora allata. Furthermore, we observed a tissue-dependent effect of the SchgrEcR/SchgrRXR knockdown on the transcript levels of the insulin receptor and neuroparsin 3 and 4. The insulin receptor transcript levels were upregulated in the brain, but not the fat body and gonads. Neuroparsins 3 and 4 transcript levels were down regulated in the brain and fat body, but not in the gonads.